Utilisation Of Organic Acids From Anaerobically Treated Palm Oil Mill Effluent With And Without Sludge Recycle For Polyhydroxyalkanoate Production - Sim, Kean Hong (2003)
Two-stage fermentation was carried out in this study where palm oil mill effluent (POME) was used as substrate for volatile fatty acids (VFA) production by continuous anaerobic treatment using a 50 L continuous stirred tank reactor (CSTR). The VFA obtained were then used for polyhydroxyalkanoate (PHA) production by Ralstonia eutropha ATCC 17699. Three experiments were conducted in anaerobic treatment of POME until steady state was achieved, i.e. (1) pH 6.5, 30"C, 80 rpm, sludge/POME ratio 1: 1, hydraulic retention time (HRT) 4 days, without sludge recycle and POME was fed continuously; (2) pH 6.5, 30"C, 100 rpm, sludge/POME ratio 1:1, HRT 4 days, without sludge recycle and POME was fed manually three times a day; (3) pH 5.5, 30°C, 150 rpm, sludge/POME ratio 3:7, HRT 4 days, SRT 8.2 days with partially sludge recycled (500 mL) and POME was fed manually three times a day. The major acids produced were acetic, propionic and butyric acids. The highest amount of VF A obtained were 15.36 g/L in 2nd experiment, followed by 1st experiment with 15.04 g/L and finally 1023 g/L in 3rd experiment For 2nd and 3rd experiments, COD removal was low which values at 12 5% and 31 1 % while BOD yield were 58 3% and 43.4% respectively.